1987
DOI: 10.1111/j.1476-5381.1987.tb11231.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of vasoconstriction induced by platelet‐activating factor in guinea‐pig perfused hearts by selective platelet‐activating factor receptor antagonists

Abstract: 1 Platelet-activating factor (Paf) is a potent coronary vasoconstrictor in rat, guinea-pig, dog and pig.The present study investigated the mechanism and duration of action of Paf in guinea-pig isolated, Krebs-perfused hearts. 2 Dose-related and sustained decreases in cardiac contractility and increases in coronary perfusion pressure were elicited by bolus doses of Paf (0.3-100 pmol). 3 Platelet-activating factor (30 pmol) induced increases in the production of immunoreactive thromboxane B2 (TXB2), leukotriene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In most experiments, a single bolus dose of 300 3000 platelet-activating factor (Paf, 100pmol) was administered to increase the coronary perfusion pressure and thereby facilitate the measurement of vasodila-3.0pmol) and tor responses. The Paf-induced increase in perfusion la generation pressure was stable for at least 3 h as previously ols) of indo-observed (Piper & Stewart, 1986;1987b (Piper & Stewart, 1987a). None of the drugs used in this study interfered in the i to discover radioimmunoassay of 6-oxo-PGF10.…”
Section: Introductionsupporting
confidence: 80%
“…In most experiments, a single bolus dose of 300 3000 platelet-activating factor (Paf, 100pmol) was administered to increase the coronary perfusion pressure and thereby facilitate the measurement of vasodila-3.0pmol) and tor responses. The Paf-induced increase in perfusion la generation pressure was stable for at least 3 h as previously ols) of indo-observed (Piper & Stewart, 1986;1987b (Piper & Stewart, 1987a). None of the drugs used in this study interfered in the i to discover radioimmunoassay of 6-oxo-PGF10.…”
Section: Introductionsupporting
confidence: 80%
“…Piper & Stewart (1986& Stewart ( , 1987 showed that indomethacin attenuated the increase in perfusion pressure in rat and guinea-pig isolated hearts following bolus injections of PAF. It had also been reported that indomethacin blocked the coronary vasoconstriction produced by intracoronary injection of PAF in the pig heart in vivo (Feuerstein et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of these studies are diverse. PAF was shown to cause vasoconstriction in the guinea-pig perfused heart (Levi et al, 1984;Piper & Stewart, 1987) and in the rat perfused heart (Piper & Stewart, 1986). In contrast, intracoronary injection of PAF to anaesthetized dogs produced only increases in coronary flow and this effect was reduced after the removal of circulating platelets (Jackson et al, 1986).…”
Section: Introductionmentioning
confidence: 99%